INGLISH LANGUAGE NEEDS FOR MEDICAL STUDENTS - Buranova Dilafruz Djamaldinovna (Galaxy International Interdisciplinary Research Journal, 2024)
The work of an English teacher at a medical university is faced with various types of teaching activities. The most of them may require the use of well-organized teaching methods, as well as innovative forms of education. The main task of an English teacher is not only to have pedagogical skills, but also to pay attention to the needs of each student when learning the language in the context of his future specialty. This study aims to identify possible factors of their language needs and effective learning strategies of English.